KANDUNGAN LOGAM BERAT PADA ANGGUR LAUT (Caulerpa lentilifera) BUDIDAYA DAN ALAM - Aura Ramadhanti Purenji; Kadek Lila Antara; Made Dwipa Kusuma Maharani (Jurnal Media Akuakultur Indonesia, 2023)
Seaweed commodities are one of the products in the fisheries and marine sector that has the potential to be developed. One type is sea grape or commonly known as Caulerna lentillifera which is very widely spread in waters throughout Indonesia. This research method is descriptive quantitative, this research was conducted to determine the heavy metal content in natural sea grapes and cultivated sea grapes. The research procedure consisted of pre-research process to observation and checking of heavy metal content. The results of research on heavy metal content of cultivated sea grapes get good results, while for nature there are levels of heavy metals Pb so it can be said that it is not very good. The results of measuring the length of ramuli in the first week was 3.3 cm, the second week was 4.4 cm then increased in length in the third week to 5.8 cm, and ended in the fourth week with an increase in length of 6.9 cm. The results of the calculation of the number of ramuli in week 1 showed that the average number of ramuli was 12, the average number of ramuli in the first week increased to 14 in the second week and increased in the third week to 17 then ended in the fourth week with an average of 19 ramuli. The quality of water used in the cultivation of sea grapes in Musi Village and natural sea grapes is still in normal status.